2012
DOI: 10.1007/s00464-012-2625-5
|View full text |Cite
|
Sign up to set email alerts
|

Quality-of-life measures after single-access versus conventional laparoscopic cholecystectomy: a prospective randomized study

Abstract: This study supports other studies that show that SALC is a feasible and promising alternative to traditional laparoscopic cholecystectomy in selected patients with better cosmesis, QOL, and improved postoperative pain results, and it can be performed with the existing laparoscopic instruments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 22 publications
2
41
0
Order By: Relevance
“…Almost all of these studies concluded that there is no difference between SP-LS and conventional LS in the QoL. Just a few studies suggested that SP-LS improves the QoL at an immediate postoperative state (B1 week) [9,12]. Our results are consistent with these findings.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Almost all of these studies concluded that there is no difference between SP-LS and conventional LS in the QoL. Just a few studies suggested that SP-LS improves the QoL at an immediate postoperative state (B1 week) [9,12]. Our results are consistent with these findings.…”
Section: Discussionsupporting
confidence: 83%
“…There are several reports on the QoL effect of SP-LS for appendectomy or cholecystectomy in general surgery [9][10][11][12][13]. Almost all of these studies concluded that there is no difference between SP-LS and conventional LS in the QoL.…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued against single port laparoscopy that there could be a higher rate of incisional hernia. [26][27][28][29][30][31] We did not find any such difference, and we actually believe that it is easier to close the fascial wound after single port laparoscopy because the larger skin incision facilitates the closing. Longer follow-up time should in any case be employed to re-evaluate whether incisional hernia rates continue to be equal in both groups.…”
Section: Discussionmentioning
confidence: 65%
“…Aprea et al reported that SILC and CLC patients were not different in severity of postoperative pain [9]. Also, Ma et al claim that SILC procedures are longer, associated with more postoperative complications and pain, and are not superior in QOL compared to CLC procedures [14,15].…”
Section: Discussionmentioning
confidence: 98%